Same time next summer [large type] - Monaghan, Annabel (Thorndike Press, a part of Gale, a Cengage Company, 2023)
"Sam's life is on track. She has the perfect doctor fiance, Jack, a great job in Manhattan, and is about to tour a wedding venue near her family's Long Island beach house. Everything should go to plan, yet the minute she arrives, Sam senses something is off. Wyatt is here. Her Wyatt. But there's no reason for a thirty-year-old engaged woman to feel panicked around the guy who broke her heart when she was seventeen. Right? Yet being back at this beach, Sam remembers who she used to be, and as Wyatt re-enters her life, their connection is as undeniable as it always was. She will have to make a choice" --